2011
DOI: 10.1159/000328869
|View full text |Cite
|
Sign up to set email alerts
|

Cardiospecific microRNA Plasma Levels Correlate with Troponin and Cardiac Function in Patients with ST Elevation Myocardial Infarction, Are Selectively Dependent on Renal Elimination, and Can Be Detected in Urine Samples

Abstract: Objectives: Circulating microRNAs (miRNAs) are promising as biomarkers for various diseases. We examined the release patterns of cardiospecific miRNAs in a closed-chest, large animal ischemia-reperfusion model and in patients with ST elevation myocardial infarction (STEMI). Methods: Six anesthetized pigs were subjected to coronary occlusion-reperfusion. Plasma, urine, and clinical parameters were collected from 25 STEMI patients undergoing primary percutaneous coronary intervention. miRNA was extracted and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
202
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(217 citation statements)
references
References 59 publications
10
202
0
1
Order By: Relevance
“…In humans, 25 patients with MI revealed that all four miRNAs were increased in plasma, with a peak at 12 h. Peak values of miR-208b correlated with peak troponin levels. miR-1 and miR-133a both correlated strongly with renal elimination, which was confirmed by detection of miR-1 and miR-133a, but not miR-208b or miR-499-5p, in the urine [85] .…”
Section: Plasma and Urine Mirnasmentioning
confidence: 57%
“…In humans, 25 patients with MI revealed that all four miRNAs were increased in plasma, with a peak at 12 h. Peak values of miR-208b correlated with peak troponin levels. miR-1 and miR-133a both correlated strongly with renal elimination, which was confirmed by detection of miR-1 and miR-133a, but not miR-208b or miR-499-5p, in the urine [85] .…”
Section: Plasma and Urine Mirnasmentioning
confidence: 57%
“…20 Analysis of 25 patients with ST elevation myocardial infarction (STEMI) revealed that miR-208b strongly correlated with troponin level and the ejection fraction. 21 In the same study authors registered high level of miR-1, miR-133a, miR-208b and miR-499-5p in plasma of patients, and what more interesting, miR-1and miR-133a was detected in urine of patient with STEMI. 21 This data indicate that not only circulating miRNAs in blood but also in other fluids like urine are very promising for heart pathology diagnosis.…”
Section: Introductionmentioning
confidence: 79%
“…21 In the same study authors registered high level of miR-1, miR-133a, miR-208b and miR-499-5p in plasma of patients, and what more interesting, miR-1and miR-133a was detected in urine of patient with STEMI. 21 This data indicate that not only circulating miRNAs in blood but also in other fluids like urine are very promising for heart pathology diagnosis. Other group of authors identified four miRNAs which strongly discriminated patients with chronic heart failure from controls: miR-660-3p, miR-665, miR-1285-3p and miR-4491.…”
Section: Introductionmentioning
confidence: 79%
“…Four studies so far in European populations in vivo 32: 313-318 (2018) correlating altered miR expression with specific types of myocardial infarction are reported in the literature: a Swedish, a Belgian, an Italian and a German. In the study of Gidlöf et al (27), miR-208b and miR-499 increased abruptly in plasma of ST elevation myocardial infarction (STEMI) patients, but not in their urine. Furthermore, Devaux and his colleagues found miR-208b and miR-499 highly increased in MI patients and nearly undetectable in healthy controls (28).…”
Section: Plasma Levels Of Mir208b (A) and Mir499 (B) Were Significantmentioning
confidence: 99%